A study on the employment status of agency-hired employees in government offices - Cabanus, Catherine; Javier, Ana Marie; Gonzales, Hanna Grace; Mecenas, Rutherine; Tipawan, Almira (2003.)
The study is all about the employment status of agency-hired employees in the government offices. Specifically, the nature of their jobs, the benefits they received, and the policies imposed to them by the agency and the government offices they are working with. The respondents of the study are the agency-hired employees from different government offices in Iloilo City such as SSS, GSIS, Pag-Ibig, UPV - Iloilo and DOLE. The respondents are mostly security guards, clerical workers and utility workers of different agencies deployed in different government offices. The study will show the advantages and disadvantages of being agency-hired employees.
Research Paper (Mgt 199). -- Iloilo City : University of the Philippines in the Visayas - College of Management, 2003.